Mutual influence of additives of Ca and Si on properties of Cr-doped YAG ceramics - Chaika, M.A.; Vovk, O.M.; Safronova, N.A.; Parkhomenko, S.V.; Doroshenko, A.G.; Tolmachev, A.V. (Functional Materials, 2016)
Cr-doped yttrium aluminum garnet ceramics with different concentration of additives Ca and Si were synthesized by vacuum reaction sintering. It was established that simultaneous doping with Ca and Si effects crucially on morphology and optical ceramics properties. Average grain size of such ceramics can reach to 1.08±0.06 μm that is much more less against the ceramics without Ca dopant. The optical properties of the ceramics deteriorate significantly with increase of Ca concentration. The degree of Cr4+ transformation to Cr3+ under air annealing is not well due to competition between Cr⁴⁺ and Si⁴⁺ ions to be charge compensated by Ca²⁺. Sintering aid SiO₂, which used in widespread ceramic technology to produce the high optical quality ceramics based on YAG, cannot be applied to produce the Cr⁴⁺-doped YAG ceramics with Ca as a charge compensator.